Proceedings of the 4th Asian Education Symposium (AES 2019) 2020
DOI: 10.2991/assehr.k.200513.026
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Motivation of English Language Learning Students in Indonesia

Abstract: Motivation is an essential part of the learning process especially learning a language to achieve the desired goals. This study aims to examine the English major first-year students' motivation for learning English. The method employed in this study is a case study method. The participants were 50 students from the English Department at Indonesia University of Education. The questionnaire was used as the instrument to collect the data. The findings revealed that including having significant differences between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
3
2
0
Order By: Relevance
“…1) From the online questionnaire and the interview, the results showed that the students were more instrumentally motivated rather than integratively motivated in English learning. This finding is in accordance with some previous related studies (Chuang, Weng, & Chen, 2018;Hong & Ganapathy, 2017;Radfar & Lengkanawati, 2020;Suryasa, Prayoga, & Werdistira, 2017;Syafrizal, 2019;Zhang, Dai, & Wang, 2020). A study involving Uzbekistan undergraduate students of Tashkent State University of Law conducted by Radfar and Lengkanawati (2020), as well as that by Syafrizal (2019) which was conducted for Indonesian Junior High students revealed that EFL students tended to be instrumentally motivated in the English language learning.…”
Section: Types Of High School Students' Motivation In Learning Englishsupporting
confidence: 92%
See 1 more Smart Citation
“…1) From the online questionnaire and the interview, the results showed that the students were more instrumentally motivated rather than integratively motivated in English learning. This finding is in accordance with some previous related studies (Chuang, Weng, & Chen, 2018;Hong & Ganapathy, 2017;Radfar & Lengkanawati, 2020;Suryasa, Prayoga, & Werdistira, 2017;Syafrizal, 2019;Zhang, Dai, & Wang, 2020). A study involving Uzbekistan undergraduate students of Tashkent State University of Law conducted by Radfar and Lengkanawati (2020), as well as that by Syafrizal (2019) which was conducted for Indonesian Junior High students revealed that EFL students tended to be instrumentally motivated in the English language learning.…”
Section: Types Of High School Students' Motivation In Learning Englishsupporting
confidence: 92%
“…This finding is in accordance with some previous related studies (Chuang, Weng, & Chen, 2018;Hong & Ganapathy, 2017;Radfar & Lengkanawati, 2020;Suryasa, Prayoga, & Werdistira, 2017;Syafrizal, 2019;Zhang, Dai, & Wang, 2020). A study involving Uzbekistan undergraduate students of Tashkent State University of Law conducted by Radfar and Lengkanawati (2020), as well as that by Syafrizal (2019) which was conducted for Indonesian Junior High students revealed that EFL students tended to be instrumentally motivated in the English language learning. In addition, another research conducted by Hong and Ganapathy (2017) also suggested that ESL students of a secondary school in Malaysia were generally instrumentally motivated.…”
Section: Types Of High School Students' Motivation In Learning Englishsupporting
confidence: 92%
“…What was performed by the participant exemplified that integrative motivation emerged from learner's engagement on culture and community's acceptance due to the interest of interaction with people by learning about their culture and language (Brown, 2001;Chalak, A., Kassaian, 2010;Mun, 2011). Thus, this finding also correlates to Radfar & Lengkanawati's (2020) finding that one of the integrative aspects deals with learner's interest in learning English.…”
Section: Learners' Motivation In Learning English At Non-formal Educationsupporting
confidence: 82%
“…This aligns with Indonesian context, where English is a foreign language. Surprisingly, even English Education majors in Indonesia demonstrate stronger instrumental motivation than integrative motivation (Radfar & Lengkanawati, 2020). Similar findings emerge from Chadian Cameroon, where English learners show a positive attitude towards the language, but prioritize practical goals like international travel (Safotso & Tompté, 2018).…”
Section: Experience English Immersion and Culturementioning
confidence: 72%
“…The formation of English-language communities can play a crucial role in fostering integrative motivation, providing a comfortable environment for self-expression and skill development (Radfar & Lengkanawati, 2020;Orfan, 2020). These spaces offer a positive and enjoyable learning experience that can significantly improve students' attitudes (Orfan, 2020).…”
Section: Experience English Immersion and Culturementioning
confidence: 99%